Root And Shoot Development During the Plant Crop and The First Ratoon of Banana and Plantain (Musa Spp.) With Implications for Perennial Cultivation on Degraded Ultisols in South-Eastern Nigeria. - Blomme, Guy; Swennen, Rony; Turyagyenda, Laban Frank; Tenkouano, Abdou (ACORBAT, 2006)
The effect of cycle on root system and shoot development was studied for two crop cycles (plant crop and first ratoon). The study revealed that shoot and root system development declined from the plant crop to the first ratoon for plants grown on degraded Ultisols in south-eastern Nigeria.
Keywords: plant crop; root system; ratoon crop